Editor Preferences for the Use of Scientific Information in Livestock Publications - Traci L. Naile; D. Dwayne Cartmell (Journal of Applied Communications, 2009)
Editors of monthly livestock publications were surveyed to determine their perceptions of the amount, type, and sources of scientific information used in their respective publications. The most important scientific topics to editors were animal health, management, and breeding and genetics. Editors’ identification of the most important topics agreed with previously reported audience perceptions of information needs and previous studies of information provided by agricultural journals, although lower rankings of policy and worker/employee safety information contradicted the importance of magazines identified by audiences in previous studies. The importance of certain gatekeeping criteria to editors reflected the general standards of accuracy and newsworthiness found in journalism, as well as editors’ perceptions of their livestock audiences’ information needs. A majority of editors recommended two to four sources be used in a scientific story, with university faculty or staff, Cooperative Extension, veterinarians and the USDA identified as the top sources. The number and sources of information preferred coincided with source characteristics as criteria for using scientific information. The specific sources most preferred by editors also demonstrated the orientation of editors with other gatekeepers and the audience in selecting appropriate information for publication. Scientific information published was similar to editors’ rankings of topic importance and source preferences. Scientific information was written for the average producer, and a majority of editors reported publishing scientific stories in at least one-half of issues. The depths and overall use of scientific information also supported the importance of delivering understandable scientific information to their agricultural audiences.